Making Better Decisions Balancing Conflicting Criteria - Korhonen, Pekka J.; Wallenius, Jyrki; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book offers a comprehensive introduction to decision-making in an MCDM framework. Designed as a tutorial, it presents the main concepts and methods to be applied, together with essential background information. This includes the concept of nondominance, Simon$1 (Bs bounded rationality, Tversky and Kahneman$1 (Bs prospect theory, and the concepts of behavioral vs. mathematical convergence and premature stopping put forward by Korhonen, Moskowitz and Wallenius. The book concludes with a non-technical review of many popular decision algorithms, including the Analytic Hierarchy Process (AHP), VIMDA, and a number of classic interactive man-machine algorithms. In essence, the book is a (3z(Bone-stop(3y (Bsource on everything you need to know about managerial decision-making in the multiple-criteria setting.s
Different Paradigms of Decision-Making -- About the Role of Intuition -- Towards Analytic Decision-Making -- How Do Humans Make Choices? -- Beware of Decision Traps: The World of Certainty -- Beware of Decision Traps: The World of Uncertainty -- The Devil is in the Details -- A Picture is Worth a Thousand Words -- Choosing Among Known Alternatives -- Designing Potential Solutions -- Solving Design Problems -- Need for Decision Support Systems -- Use Scenarios Instead of a Crystal Ball -- Making Operations More Efficient -- Real-World Problems -- Negotiating a Deal -- In Conclusion.
Keywords: Operations research; Decision making; Management science; Industrial psychology; Behavioral economics; Operations Research/Decision Theory; Operations Research, Management Science; Industrial and Organizational Psychology; Behavioral/Experimental Economics